PERANCANGAN PEMBUATAN BALANCING ROBOT DENGANARDUINO DAN GYRO SENSOR - BAYU PRASETYO, OKY; Budiarso, Zuly (Information Technology and Telematics, 2018)
ABSTRAK balancing a robot called a robot that has two wheels on both sides and will not be stable without good control. When balancing a two-wheeled stereo robot forward or tilted to the right, what needs to be done is that the motor will turn the clock from the two-wheeled robot balancing to rotate in the front direction. The style used to balance the results of the wheel rotation. The use of Arduino Uno as the main controller, DC motor as a mechanical drive output, Sharpgp GP11 proximity sensor to detect objects. The information signal along with the Accelerometer and Gyroscope sensors on the MPU6050-based IMU Sensor is read by an ATMEGA16 AVR microcontroller via I2C communication. The results of reading the IMU data through I2C communication show the Self-Balancing Robot activity in the measurement of Pitch and Roll data parameters is 0 degree.